2011
DOI: 10.1002/chem.201101104
|View full text |Cite
|
Sign up to set email alerts
|

Giant Deuteron Migration During the Isosymmetric Phase Transition in Deuterated 3,5‐Pyridinedicarboxylic Acid

Abstract: Deuterated 3,5-pyridinedicarboxylic acid exhibits reversible temperature-induced deuteron migration of a magnitude unprecedented in this class of compounds. We used a combination of variable-temperature powder and single-crystal neutron diffraction and density functional theory (DFT)-based computational methods to elucidate the origin of this remarkable behaviour. Single-crystal neutron diffraction shows that between 15 and 300 K, the deuteron moves by 0.32(1) Å and the structure changes from a low-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…9 Urea-phosphoric acid is one of only two proton migration materials studied extensively using a combination of experimental techniques and theory, the other being pyridine-3,5dicarboxylic acid. 7,11,12 While the migration has not been attributed to increased thermal motion in either of these examples, this cannot be ruled out as a possible explanation in other materials exhibiting migration.…”
Section: Introductionmentioning
confidence: 83%
“…9 Urea-phosphoric acid is one of only two proton migration materials studied extensively using a combination of experimental techniques and theory, the other being pyridine-3,5dicarboxylic acid. 7,11,12 While the migration has not been attributed to increased thermal motion in either of these examples, this cannot be ruled out as a possible explanation in other materials exhibiting migration.…”
Section: Introductionmentioning
confidence: 83%
“…For example, two sulfathiazole-oxalic acid complexes have been shown to be salts by multinuclear SS-NMR (Koike et al, 2014) and recently a furosemide-isonicotinamide complex was confirmed to be a cocrystal by comparison of 15 N SS-NMR and DFT-calculated chemical shifts (Kerr et al, 2015). Another aspect of the study of proton position is the characterization of reversible proton migration over short strong hydrogen bonds, which is of fundamental interest but also potentially relevant to some types of functional materials (Ford et al, 2011;Frantsuzov et al, 2014).…”
Section: Tablementioning
confidence: 99%
“…At higher temperature the apparent dynamical rate saturates above 110 K whereas it could be expected to continue to increase given that diffraction [40], nuclear quadrupole resonance [50], and vibrational spectroscopy [51] report the crossover from donor to acceptor species at 200 K. Similarly, the temperature dependence of the spectral density amplitude [ Fig. 3(b)] shows a clear maximum at 105 K. In the usual model [21], in which …”
mentioning
confidence: 94%
“…The intermolecular HB has a N-O distance of 2.54 Å and lies in the few percent of the shortest known N − H Á Á Á O HBs [37,38]. The proton is almost centered and is clearly observed in neutron diffraction [39,40] to migrate from the donor N at low temperature to the acceptor O at room temperature. The proton jump distance is 0.1 Å in the protonated crystal and at 200 K the proton is, on average, centered.…”
mentioning
confidence: 99%